f(x+1)=9x+4

Simple and best practice solution for f(x+1)=9x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x+1)=9x+4 equation:


Simplifying
f(x + 1) = 9x + 4

Reorder the terms:
f(1 + x) = 9x + 4
(1 * f + x * f) = 9x + 4
(1f + fx) = 9x + 4

Reorder the terms:
1f + fx = 4 + 9x

Solving
1f + fx = 4 + 9x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Reorder the terms:
-4 + 1f + fx + -9x = 4 + 9x + -4 + -9x

Reorder the terms:
-4 + 1f + fx + -9x = 4 + -4 + 9x + -9x

Combine like terms: 4 + -4 = 0
-4 + 1f + fx + -9x = 0 + 9x + -9x
-4 + 1f + fx + -9x = 9x + -9x

Combine like terms: 9x + -9x = 0
-4 + 1f + fx + -9x = 0

The solution to this equation could not be determined.

See similar equations:

| x^2+-2x+-4=0 | | -6(2n-7)+2(n+4)=-36 | | x-2x-4=0 | | 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x | | 78=3(x)+18 | | 12c-15=11 | | 13*2+3= | | x=2y+2z+24 | | (3-u)(2u+9)=0 | | 8-5+3-4= | | Y=3x^3-2x^2-12x+8 | | 6x+25=74 |

Equations solver categories